Engineering properties and carbon footprint of ground granulated blast-furnace slag-palm oil fuel ash-based structural geopolymer concrete - Islam, A.; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin; Bashar, I.I.; Kabir, S.M.A. (Elsevier, 2015)
Engineering properties of geopolymer concrete developed using palm oil fuel ash and slag as binders, manufactured sand and quarry dust as replacement materials for fine aggregate, and oil palm shell (OPS) as coarse aggregate were investigated along with carbon footprint. The use of binder content of 425 kg/m(3) with OPS based lightweight concrete produced the highest compressive strength of 33 MPa. Ultrasonic pulse velocity of normal weight geopolymer concrete (NWGC) shows it as ``good quality''. The development of structural grade OPS geopolymer concrete comparable to NWGC shows its potential application for structural purposes. OPS geopolymer concrete has lower carbon footprint of 50-60% compared to conventional concrete. (C) 2015 Elsevier Ltd. All rights reserved.